Police Reform in a Post-Conflict Context: The Case of Solomon Islands. (31st December 2019) - Dinnen, Sinclair; Watson, Danielle
Abstract: Police reform in much of the developing world reflects a preoccupation with either shifts away from paramilitaristic policing models or restoration of law and order in post-conflict societies. For many Pacific Island Countries (PICs), dialogue on reform reflects the prioritization of internal organizational restructuring and capacity building, with minimal emphasis on responding to ever-changing stakeholder demands. What is also common is for police reform efforts to closely align with prioritized focal areas of donor countries or powerful neighbours in developed countries with different contextual realities. Here we discuss police reform efforts in a PIC that has been the recipient of a major regional post-conflict state-building intervention and highlight the complexities specific to piecing together the police reform architecture. We also make reference to Solomon Islands to support our argument that problematic police reform can be largely attributed to focal imbalances between internal and external transformation agendas. The article concludes with a summary of the constraints associated with police reform in post-conflict contexts and recommendations for navigating the reform process.